2012
DOI: 10.3399/bjgp12x636137
|View full text |Cite
|
Sign up to set email alerts
|

Delivering a national programme of anticipatory care in primary care: a qualitative study

Abstract: BackgroundPrimary prevention often occurs against a background of inequalities in health and health care. Addressing this requires practitioners and systems to acknowledge the contribution of health-related and social determinants and to deal with the lack of interconnectedness between health and social service providers. Recognising this, the Scottish Government has implemented a national programme of anticipatory care targeting individuals aged 45-64 years living in areas of socioeconomic deprivation and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Twenty-seven of 29 studies [ 19 , 21 , 23 , 24 , 34 , 37 , 38 , 40 , 57 , 58 , 61 65 , 71 , 81 , 86 , 87 , 90 , 95 98 , 101 , 117 – 120 ] including GP views as an outcome also measured either managerial views (23 studies), other MDT views (23 studies), or patient views (5 studies). Three studies evaluated the aspects of the PCMH in the USA and found difficulties in recruiting MDT members [ 118 ], anticipated staff satisfaction [ 117 ], and identified important training to assist with PCMH implementation (Table 2 ) [ 119 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-seven of 29 studies [ 19 , 21 , 23 , 24 , 34 , 37 , 38 , 40 , 57 , 58 , 61 65 , 71 , 81 , 86 , 87 , 90 , 95 98 , 101 , 117 – 120 ] including GP views as an outcome also measured either managerial views (23 studies), other MDT views (23 studies), or patient views (5 studies). Three studies evaluated the aspects of the PCMH in the USA and found difficulties in recruiting MDT members [ 118 ], anticipated staff satisfaction [ 117 ], and identified important training to assist with PCMH implementation (Table 2 ) [ 119 ].…”
Section: Resultsmentioning
confidence: 99%
“…S6). Twenty reported on outcomes of PCT for those living in deprived areas [ 6 , 21 , 24 , 25 , 30 , 31 , 48 , 49 , 52 , 63 , 69 , 77 , 78 , 83 , 88 , 95 , 102 , 110 , 116 , 117 ]. Three of these [ 48 , 49 , 52 ], reporting on the Chinese 2009 Health Care Reform, showed increased primary care access, particularly in low-income areas, and increased demand for services.…”
Section: Resultsmentioning
confidence: 99%
“…and Dickeya spp. can coexist in infected plant tissues [ 29 31 ], although there is little information on the relative importance of any synergistic effect in disease development [ 32 ]. It has been suggested that bacteria from both genera may interact in plants to facilitate infection [ 31 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such disparity ultimately serves to exacerbate rather than ameliorate inequalities in a multiply disadvantaged population (O'Donnell et al . ).…”
Section: Discussionmentioning
confidence: 97%